FRAMEWORK FOR USER INVOLVEMENT IN HEALTH TECHNOLOGY ASSESSMENT AT THE LOCAL LEVEL: VIEWS OF HEALTH MANAGERS, USER REPRESENTATIVES, AND CLINICIANS. (8th May 2015) - Gagnon, Marie-Pierre; Desmartis, Marie; Gagnon, Johanne; St-Pierre, Michèle; Rhainds, Marc; Coulombe, Martin; Tantchou, Mylène Dipankui; Légaré, France
Abstract : Objectives: The aim of this study was to explore stakeholders' points of views regarding the applicability and relevance of a framework for user involvement in health technology assessment (HTA) at the local level. We tested this framework in the context of the assessment of alternative measures to restraint and seclusion among hospitalized adults and those living in long-term-care facilities. Methods: Twenty stakeholders (health managers, user representatives, and clinicians) from seven regions of Quebec participated in a semi-structured interview. A thematic analysis of the transcribed interviews was performed. Results: The findings highlighted the relevance and applicability of the framework to this specific HTA. According to interviewees, direct participation of users in the HTA process allows them to be part of the decision-making process. User consultation makes it possible to consider the views of a wide variety of people, such as marginalized and vulnerable groups, who do not necessarily meet the requirements for participating in HTA committees. However, some user representatives emphasized that user consultation should be integrated into a more holistic and participatory perspective. The most frequent barrier associated with user involvement in HTA was the top-down health system, which takes little account of the user's perspective. Conclusions: The proposed framework was seen as a reference tool for making practitioners and health managers aware of the different mechanisms of user involvement in HTA and providing a structured way to classify and describe strategies. However, there is a need for more concrete instruments to guide practice and support decision making on specific strategies for user involvement in HTA at the local level.